Reverse genotyping: unveiling Alu element insertion as a new cause of Kabuki syndrome using DNA methylation signature - Quentin Sabbagh; Nathalie Ruiz-Pallares; Cassandra Rastin; Jacques Puechberty; Thomas Guignard; Claire Jeandel; Fanny Merklen; Pascal Pujol; Jennifer Kerkhof; Bekim Sadikovic; Mouna Barat-Houari; David Geneviève (Clinical Epigenetics)
Abstract Kabuki syndrome type 1 (KS1) is a monogenic disorder arising from pathogenic variants within KMT2D and characterized by syndromic neurodevelopmental delay. We report the retrospective identification of a causative AluY insertion within KMT2D in a genetically unsolved individual with typical KS1 features, after identification of a DNA methylation signature. This is the first documentation of Alu insertion as a molecular mechanism responsible for KS1. This study emphasizes the need for reanalyzing inconclusive sequencing data in individuals with gene-specific phenotypes and reinforces episignature as a reliable diagnostic tool when NGS approaches fail to provide conclusive results in individuals with rare diseases.